INDONESIA LOGISTICS SECTOR REVIEW: PERFORMANCE, CHALLENGES, AND FUTURE GROWTH - Handy Bugiman; Tota Pirdo Kasih; Zheng Kai (RADJA PUBLIKA, 2026)
This paper provides a comprehensive review of Indonesia's logistics sector, analyzing its performance, structural challenges, and strategic outlook through 2030. As the world's largest archipelago with a robust GDP growth of 5% in 2024, Indonesia possesses a resilient domestic market yet faces significant hurdles in logistics efficiency. The study highlights that Indonesia ranks 61st in the World Bank's Logistics Performance Index (LPI), lagging behind ASEAN peers due to critical bottlenecks in customs clearance and physical infrastructure. To address these issues, the sector is currently being reshaped by a